CEO education and firm performance: Evidence from corporate universities - Nguyen Hai Long; Pengda Fan (Administrative Sciences, 2022)
Corporate universities are increasingly being established in response to corporate dissatisfaction with the knowledge provided by traditional universities. While some argue that they may pose the greatest threat to traditional universities, others propose that corporate universities might provide better undergraduate-level education than traditional universities. To this end, this research tries to answer the following research question: can integrating corporation education into traditional universities provide better educational outcomes? Using a sample of 40,563 firm-year observations from 2001 to 2019 and exploiting the unique setting of Japanese corporate universities, the authors find that the CEOs who are graduates of corporate universities significantly underperform compared to their counterparts graduating from traditional universities. The results are robust under various alternative estimations, such as general method of moments (GMM) IV regressions and propensity score matching. Overall, the results indicate that integrating corporation needs into traditional higher education will lead to lower individual productivity.
Keywords: 350; CEO education; corporate university; firm performance